2012
DOI: 10.1016/j.juro.2012.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Nephron Sparing Surgery for Unilateral Wilms Tumor in Children with Predisposing Syndromes: Single Center Experience Over 10 Years

Abstract: Nephron sparing surgery appears safe for patients with unilateral Wilms tumor associated with predisposing syndrome(s), allowing for the preservation of renal function and good oncologic outcomes for the available followup time. If more studies confirm our observation, current recommendations for the surgical treatment of Wilms tumor may need to reemphasize the value of attempting nephron sparing surgery in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Adequate oncological outcomes have been reported with this approach [25]. NSS can safely be done after previous partial nephrectomy, further preserving renal parenchyma whereas patients are still at risk for developing WT (Fig.…”
Section: Wt In Patients With Predisposition Syndromesmentioning
confidence: 99%
“…Adequate oncological outcomes have been reported with this approach [25]. NSS can safely be done after previous partial nephrectomy, further preserving renal parenchyma whereas patients are still at risk for developing WT (Fig.…”
Section: Wt In Patients With Predisposition Syndromesmentioning
confidence: 99%
“…To summarize, the current study found no clear advantage to nephron sparing surgery over total nephrectomy in reducing the risk of renal complications, but due to the small number of cases, further observation should be undertaken [7,8]. Special attention should be paid to patients treated with cyclophosphamide and carboplatin [16].…”
Section: Discussionmentioning
confidence: 66%
“…According to the current therapeutic protocol, the most commonly performed operating procedure is total nephrectomy. In certain circumstances it is possible to perform partial nephrectomy (nephron sparing surgery, NSS) [7,8]. Indications for this type of procedure are mainly tumors at low clinical stages, lesions localized peripherally (not in the middle), and small lesions in bilateral Wilms' tumor cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, nephron sparing is also of particular interest for children with syndromic Wilms tumor, who are at risk for multiple malignancies or renal failure from other causes. Romão et al [2] found unilateral partial nephrectomy to be safe for these patients, providing both good oncologic results and preserved renal function. Preservation of renal function is also better among children with non-syndromic Wilms tumor who undergo partial nephrectomy compared with radical nephrectomy [3].…”
Section: Discussionmentioning
confidence: 99%